2010
DOI: 10.1143/jjap.49.046502
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Pretreatment on Fixed Charge at the Silicon Nitride/Silicon Interface

Abstract: The effect of plasma treatment prior to hydrogenated amorphous silicon nitride (a-SiN:H) deposition on the a-SiN:H/Si interface was studied. NH3, NH3+N2, and NH3+H2 were used as source gases for plasma treatments. Nitridation of silicon surfaces after plasma treatment was observed by X-ray photoelectron spectroscopy (XPS). Fourier transform infrared spectroscopy (FTIR) measurement revealed that the stoichiometry of the thin nitrided layer varied depending on the source gas. After the plasma treatment and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Above 425 1C silicon nitride is formed at the Si surface whose formation increases with temperature. That this nitridation has indeed a direct relation with Q f was shown by Takakura, though he did not observe a difference in D it [8].…”
Section: Introductionmentioning
confidence: 76%
“…Above 425 1C silicon nitride is formed at the Si surface whose formation increases with temperature. That this nitridation has indeed a direct relation with Q f was shown by Takakura, though he did not observe a difference in D it [8].…”
Section: Introductionmentioning
confidence: 76%
“…It has been shown in the past that the interface properties and the fixed charge density are a sensitive function of the ammonia pre-treatment parameters [19]. It was demonstrated recently that the plasma pre-treatment on ptype (1 1 1) Si reduces the D it , irrespective of the source gases, whereas the fixed charge at the SiN x /Si interface depends on the stoichiometry of the thin nitrided layer [20]. From the above, it can be concluded that further studies are required to optimize the ammonia pre-treatment for planar (1 1 1) and textured n-type SiN x /Si interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal value of x and hence n, is very dependent upon the type of solar cell, the optimal wavelength, the texture, the module fabrication etc, for example in air a value of n=1.9 is optimal, however generally in solar cells in modules values of n = 2.04 -2.08 are preferred 7,8 .…”
Section: Introductionmentioning
confidence: 99%